2021
DOI: 10.4018/jgim.20220301.oa7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Country-of-Origin Image and Purchase Intention in Cross-Border E-Commerce

Abstract: Product country-of-origin (COO) is now playing a central role in consumers’ purchase behavior. Previous studies have investigated several factors that impact COO. However, little attention has been paid to the impact of COO on consumers’ product evaluation on Chinese products, especially in the cross-border e-commerce context. Using a multi-methods design, this study first unearthed the antecedents of COO image towards Chinese products from the qualitative data in Study 1 by drawing on the legitimacy theory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Only one study was found to adopt mixed methods combining both qualitative and quantitative approaches, that is, interviews and surveys (Bao et al, 2022). The results of the qualitative stage informed the conceptualization and operationalization in the subsequent quantitative stage.…”
Section: Overview Of Consumer Behaviourmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one study was found to adopt mixed methods combining both qualitative and quantitative approaches, that is, interviews and surveys (Bao et al, 2022). The results of the qualitative stage informed the conceptualization and operationalization in the subsequent quantitative stage.…”
Section: Overview Of Consumer Behaviourmentioning
confidence: 99%
“…For instance, individual capabilities, such as self-efficacy in international online shopping (Han et al, 2018) and exploitative and explorative IT use (Han & Kim, 2019), were stimuli triggering purchase intention. The desire for uniqueness (Han et al, 2018), ethnocentrism (Bao et al, 2022) and disposition to trust (Tikhomirova et al, 2021) have been highlighted…”
Section: Inner Cbec Ecosystem Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…He believed that the O2O (Online To Offline) mode was the best mode for cross-border e-commerce B2C selling high-priced products. Bao [20] mined the antecedent variables of the impact of the Chinese product image on consumption intention from qualitative data and then developed a contextual model of consumer product evaluation and purchase intention. The results show that cross-border e-commerce platforms could enhance consumers' willingness to consume Chinese products by improving product quality, cost control, brand image, and enterprise strength.…”
Section: Introductionmentioning
confidence: 99%